2023
DOI: 10.3389/fvets.2023.1166015
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the temporal dynamics of rumen bacterial and fungal communities in yaks (Bos grunniens) from 5 days after birth to adulthood by full-length 16S and 18S rRNA sequencing

Abstract: The rumen of ruminants is inhabited by complex and diverse microorganisms. Young animals are exposed to a variety of microorganisms from their mother and the environment, and a few colonize and survive in their digestive tracts, forming specific microflora as the young animals grow and develop. In this study, we conducted full-length sequencing of bacterial and fungal communities in the rumen of pastured yaks of different ages (from 5  days after birth to adulthood) using amplified sequencing technology. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…However, one study used 16S and 18S rRNA to sequence rumen microorganisms of yaks aged from 7 days to 12 years, and found that archaea were detected only after 14 days of age [19], which was inconsistent with this study, possibly due to different detection methods. We also found that the dominant phyla were Bacteroidetes and Firmicutes across all ages, which is in accordance with other recent studies on yaks [63]. In the 1 d and 20 d groups, the bacterial phylum Proteobacteria was significantly more numerous than that in other ages, which was consistent with previous studies that facultative anaerobic Proteobacteria are more adapted to the liquid-based dietary stage of early life [64,65].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, one study used 16S and 18S rRNA to sequence rumen microorganisms of yaks aged from 7 days to 12 years, and found that archaea were detected only after 14 days of age [19], which was inconsistent with this study, possibly due to different detection methods. We also found that the dominant phyla were Bacteroidetes and Firmicutes across all ages, which is in accordance with other recent studies on yaks [63]. In the 1 d and 20 d groups, the bacterial phylum Proteobacteria was significantly more numerous than that in other ages, which was consistent with previous studies that facultative anaerobic Proteobacteria are more adapted to the liquid-based dietary stage of early life [64,65].…”
Section: Discussionsupporting
confidence: 92%
“…Rumen microbial community composition changed with the developmental stage [17,62]. However, the microbial population dynamics from newborn to adult yaks are poorly understood, as only a few studies have been reported on ruminal bacterial community in yaks from birth (5 days or 7 days after birth) to adulthood (2 years or 12 years) using 16S and 18S rRNA sequencing [19,63]. In the present study, metagenomics analysis was used to evaluate the composition and temporal dynamics of rumen microorganisms, from birth to adult, of Maiwa yak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to bacterial community, the fungi are also important components of ruminal microorganism. Ruminal fungus can fully degrade plant fiber, because it can penetrate and break the plant cell wall tissue as well as secreting a variety of cellulose degrading enzymes (Yang et al 2023 ). Hence, the ruminal fungus can decompose some lignified fibrous materials which cannot be utilized by cellulose-degrading bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Yak rumen microorganisms alter accordingly to cope with changing diets at different growth stages, with greater relative abundances of Ascomycetes and Mesomycetes, that is, fungi adapted to liquid rations during juvenile years [ 13 , 14 ]. The fungal structure changes continually; at the grazing stage, after 90 days of age, there is an increase in the relative abundance of Thelebolus , a genus that contributes to host immunity and by 180 days of age, there is an increase in the relative abundance of Penicillium , a genus with a strong cellulose-degrading capacity [ 15 ]. In addition, yaks have adapted to the plateau environment by preferentially harboring protozoa such as rumen ciliates that have evolved to digest mainly fibers [ 16 ].…”
Section: Synergistic Evolution Between Yaks and Microorganismsmentioning
confidence: 99%